A Comprehensive Study on Homicidal Deaths in a Tertiary Health Care Institution in Nellore, Andhra Pradesh - Z.Sashikanth (Indian Journal of Forensic Medicine & Toxicology, 2021)
Homicide is a serious crime committed against humans and its detection and solution is important to theentire society. Homicide may be the result of accidental, reckless or negligent acts even if there is no intentto cause harm. The present study was taken up to know the incidence of homicides in the city of Nellore andto determine the trends in committing homicides.Aim: To study the pattern of homicides and to elucidate the different aspects of homicidal deaths.Methodology: This was a retrospective study done on alleged homicide cases autopsies done in ForensicDepartment of ACSR Medical College from March 2019 to February 2020 (1 year). Data was collectedfrom 39 reports with an alleged history of homicide.All the homicide cases for which autopsies were doneexcept for homicide cases which involved death due to rash negligent act. Data was collected from thePostmortem reports of victims of homicide, police inquest reports, medical recordsand relevanthistorycollected from family members, relatives and friends was studied.Data was entered into MS excel andexpressed as frequencies and percentages.Results:Total autopsies done during the study period from March 2019 to February 2020 (1 year) were902, of which 39 were alleged homicide autopsies. Majority of the victims belonged to 21-30 age group.Majority of the homicide cases were males. Majority of the deaths were caused by blunt objects (48%). Inabout 67% of the cases the assailant was a known person. Most of the homicides were family centered anddue to quarrels. Early detection and prevention is the need of the hour.